PERANCANGAN INSTALASI PADA KIOS MENGGUNAKAN SOLAR PANEL DENGAN KAPASITAS 350WATT - Utama, Aldi Reza; M.N, Angga Septian; Dinata, Seflahir; Utomo, Luki (Innovative: Journal Of Social Science Research, 2025)
Electrical energy is one of the most important needs for human life today. Most of the resources used in Indonesia still use traditional or fossil fuels, which are resources that are harmful to the environment. Therefore, the utilization of solar energy can be done by using solar modules. Solar energy is one of the new renewable energy sources that can answer the need for alternative energy and solutions to answer the challenges of the energy crisis that occurs, because solar energy is not polluting, cannot run out, and cannot be purchased. The method used is experimental research in the form of installing an installation system based on existing planning. The design of the solar module used is installed with an off-grid system. The off-grid system is a system that utilizes sunlight directly without being connected to the PLN network. This study analyzes the potential of solar energy as a new renewable energy source in modern kiosks using solar panels. And also provides a brief and practical guide to the community to determine the right and economical specifications in installing off-grid solar panels.